(untitled) (Global Journal of Management and Business Research, 2011)
Nowadays the service dynamic environment is considered as a main point in effective marketing Although conducting efficient operation is still significant it is not sufficient for success It s essential to design service products based on customers needs pricing programmatically distributing in the suitable ways and introducing to customers actively The new competitors in markets have focused their services on the especial parts of market in line the prices communicative efforts and service delivery But they have not tried to consider all the people needs Generally the service organizations are different from manufacturing occupations in many cases Also a various way is needed to plan and execute marketing strategies So the Keywords Service service marketing mix 7p engineering service corporation marketing audit GJMBR A Classification FOR Code 150306 JEL Code L25 The Role Of Service Marketing Mix And Its Impact On Marketing Audit In Engineering And Technical Service Corporations Strictly as per the compliance and regulations of service marketing mix as 7p is used to consider the service marketing In this paper we have studied these seven factors application and their effects on marketing audit in engineering and technical service corporation